Two new species of Crocodile Skinks (Squamata: Scincidae: Tribolonotus) from the Solomon Archipelago - Rittmeyer, Eric N.; Austin, Christopher C. (Zootaxa, 2017)
We describe two new species of the scincid lizard genus Tribolonotus from the islands of Buka and Choiseul in the Solomon Archipelago, closely related to, and previously included within, T. pseudoponceleti. One species, T. parkeri sp. nov., is endemic to Buka Island and was revealed in our previous study via taxonomically focused analyses of both next-generation sequencing data and morphology. Here, we also further support the validity of this species by more taxonomically comprehensive Bayesian species delimitation of three Sanger sequenced nuclear loci. The second species, T. choiseulensis sp. nov., is endemic to Choiseul Island and was revealed by an expanded morphological data analysis. These results suggest that numerous other species found on multiple island groups in the Solomon Archipelago may similarly represent complexes of multiple, closely related species, and that the biodiversity of the region is vastly underestimated.